Using harvard graphic (Indianapolis, IN, 1990)
This book is the best-selling graphics presentation package. It supports the creation of both text and analytical charts. The package supports many customization options and allow the automation of charts with macros or templates.
Keywords: Computer drawing,Programming languages (Electronic computer)